Effects of Sponge City Development on Soil Moisture and Water Quality in a Typical City in the Loess Plateau in China - Jia, Lu; Xu, Guoce; Huang, Miansong; Li, Zhanbin; Li, Peng; Zhang, Zhenxi; Wang, Bin; Zhang, Yixin; Zhang, Jiaxin; Cheng, Yuting (Frontiers in Earth Science, 2020)
Changes in soil moisture following the establishment of sponge cities play a key role in the regulation of the relationship between surface runoff and rain resources in arid and semi-arid regions of the Loess Plateau. Based on soil moisture and rainfall monitoring data obtained at the fine-scale (per 10-cm depth and hourly), temporal and spatial variation in soil moisture under different sponge measures and their responses to rain events were analyzed, in addition to water quality changes were investigated by water sampling. The results showed, from 2000 to 2018, the area of farmland greatly decreased from 56.88 % to 5.02 % in Guyuan, while the area of construction land increased from 29.24 % to 45.96 %. The area of changes in Guyuan accounted for 63.68% of the total area. Precipitation in July and August was large, and accounted for 19.11% and 23.24% of the multi-year average precipitation, respectively. The grasslands and sunken green spaces exhibited good water retention effects, with average soil moisture of 14.40 % and 13.77 % during the study period, and 18.48 % and 15.52 % during the rain event, respectively. During the rain event, the total nitrogen (TN), ammonia nitrogen (NH3-N), available phosphorus (AP) and total phosphorus (TP) can be effectively reduced by the sunken green spaces, with average concentrations of 0.79 mg/L, 0.28 mg/L, 0.03 mg/L and 0.05 mg/L, respectively. The development of sponge measures could improve the urban ecological environment and hydrological conditions in the Loess Plateau, and increase the potential utilization of urban rainwater resources.